2024
DOI: 10.1002/alz.13741
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations with dementia‐related proteinopathy: Application of item response theory

Yuriko Katsumata,
David W. Fardo,
Lincoln M. P. Shade
et al.

Abstract: INTRODUCTIONAlthough dementia‐related proteinopathy has a strong negative impact on public health, and is highly heritable, understanding of the related genetic architecture is incomplete.METHODSWe applied multidimensional generalized partial credit modeling (GPCM) to test genetic associations with dementia‐related proteinopathies. Data were analyzed to identify candidate single nucleotide variants for the following proteinopathies: Aβ, tau, α‐synuclein, and TDP‐43.RESULTSFinal included data comprised 966 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Along the same lines, its cognate protein RGNEF has been found to localize to hallmark TDP-43-immunoreactive inclusion bodies in ALS patient spinal cord motor neurons ( 232 , 233 ). We recently found that the ARHGEF28 SNP rs80190672 was associated with LATE-NC ( 234 ). This genotype-phenotype correlation may provide another point of etiologic connection between LATE-NC and the ALS/FTLD disease continuum.…”
Section: Genetic Associations With Late-nc and Hs-amentioning
confidence: 99%
“…Along the same lines, its cognate protein RGNEF has been found to localize to hallmark TDP-43-immunoreactive inclusion bodies in ALS patient spinal cord motor neurons ( 232 , 233 ). We recently found that the ARHGEF28 SNP rs80190672 was associated with LATE-NC ( 234 ). This genotype-phenotype correlation may provide another point of etiologic connection between LATE-NC and the ALS/FTLD disease continuum.…”
Section: Genetic Associations With Late-nc and Hs-amentioning
confidence: 99%